Overview of The Burnout Potential of Employee Staff during Pandemic Times at UNITRI - Sirli Mardianna Trishinta; Wahidyanti Rahayu Hastutiningtyas; Yanti Rosdiana (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2022)
With the Covid-19 pandemic, the central government has given policies for all local governments so that the activity process is carried out from home. However, burnout can occur because this is a psychological symptom such as physical, emotional, mental fatigue and depression that can occur in worker. The purpose of the study was to determine the description of the potential for burnout of workers in employee at UNITRI during the pandemic. The research design used a quantitative description. The population of this study were all 35 employee staff at UNITRI with  purposive sampling, in order to obtain a research sample of 18 respondents. The data collection technique used an instrument in the form of a questionnaire. The data analysis method used is descriptive test. The results showed that almost all 15 respondents (83.3%) had moderate burnout potential. Future researchers are expected to conduct similar research by exploring the determinant factors of the potential for worker Burnouts.